Allopatric color forms of Scaphidium morimotoi Löbl, 1982 (Coleoptera, Staphylinidae, Scaphidiinae) endemic to the Amami Islands, the Ryukyus, Japan - Ogawa, Ryo; Matsuo, Susumu; Hoshina, Hideto; Maeto, Kaoru (Zootaxa, 2016)
The shining fungus beetle, Scaphidium amamiense Hoshina & Morimoto, 1999 is synonymized with S. morimotoi Löbl, 1982, based on a review of morphological characters and molecular analysis. This species is endemic to the Amami Islands, the Ryukyus, Japan. An almost completely melanic form (morimotoi in strict) is known only on the island Yoro-shima, where the ordinary form with reddish fasciae on the elytra (previously called amamiense) is absent. The present study suggests that the melanic form on the small island has been fixed by random genetic drift.